Teachers’ Perception on Flipped Classroom Model in Digital Literacy Era - Leni Irianti (Universitas Lancang Kuning, 2020)
This paper is aimed at investigating the teachers’ perception on Flipped Classroom Model in digital era. In the 21st century era the teachers should help the students to develop their higher-order thinking and to improve their literacy. The rapid changes of technology involve knowledge and understanding. In education, the teachers require to master current issue and also new technology to improve their professional development. Thus, the teacher should engage with the new trends in order to improve their professional development. Thus, the teacher develops students’ higher-order thinking where the students are able to think critically, creatively and innovatively to prepare them to compete in the globalized world. Recently, there is a lot of teaching model for teacher deal with current issues and technologies. One of them is Flipped Classroom Model which is known as inverted class model. The teachers give more time for the students to learn outside the class and discuss more inside the class. The role of the teacher is as a facilitator to improve the education quality. This study is based on an internet survey. It was conducted by online google form. The subject of this study is the senior high school teacher in West Java. The result is showed that the teacher responses positively toward new teaching model.